Équipements mobiles au collège : quelles appropriations par les élèves et les enseignants ? - Christelle Pauty-Combemorel; Georges-Louis Baron (Université de Provence, 2017)
This paper presents the first results of an ongoing research, led since 2013 and focusing on the appropriation path followed by teachers and students regarding laptops provided to junior high schools by local authorities in a suburb of Paris. This research has mainly an ethnographic orientation but also uses quantitative tools like questionnaires. Our results show that students do not intensively use their laptops for classroom work, but evolution is manifest, in some subject matters. This may be explained by two main factors : the first one is linked to the educational policies implemented to foster ICT use in classrooms. The other is the existence of a process where teachers follow professional development outside of the school, sometimes on an informal basis and later are able to accompany their colleagues.